Connectivism in Learning Activity Design: Implications for Pedagogically-Based Technology Adoption in African Higher Education Contexts - Kizito, Rita Ndagire (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
This paper examines the possible characteristics and the value of designing learning activities grounded in connectivism—an emerging learning theory. It is an exploratory attempt to connect the theory to the prevailing technology adoption archetypes used in African contexts with the aim of extracting influences that could shape pedagogical technology adoption in African higher education contexts. A reflection on the process of designing learning activities that employ blogging in an experimental training intervention provides a unique context in which to try and infuse connectivist principles while outlining the challenges that surface. The questions driving the argument in this paper include: What do connectivist perspectives offer learning activity design and practice? What can the prevailing technology adoption models used in African contexts offer to learning activity design? Can we combine connectivist perspectives and African-based technology adoption models to inform pedagogical technology adoption in African higher education contexts? These questions are exploratory and are based on one single subjective experience of the author. They are part of an argument put forward as a proposal which is yet to be tested in practice.